DIFFERENCES IN THE FATTY ACID COMPOSITION OF RAT LIVER AND BRAIN TISSUES IN AN EXPERIMENTAL MODEL OF TYPE 2 DIABETES MELLITUS - Osadchuk, Yulia; Dovhan, Roman; Vershuta, Olexandr (The Ukrainian Scientific Medical Youth Journal, 2020)
One of the popular approaches to reproducing the model of type 2 diabetes mellitus (T2D) in experimental animals is a food load with a high content of natural fat since the long-term effect of increased levels of fatty acids (FA) plays a key role in the development of insulin resistance. Study of the features of the fatty acid composition of rat liver and brain tissue in an experimental model of T2D was the purpose of the work. An experimental model was reproduced on white Wistar rats by a 3-month high-fat diet (45% animal fat) supplemented with fructose and subsequent induction with streptozotocin (STZ) 25 mg/kg once. The control group (CG) consisted of intact animals that received standard vivarium food throughout the experiment. The study of the composition of FA was carried out by gas-liquid chromatography. Statistical data processing was performed using a license package IBM SPSS Statistics 23. In rats with T2D, in comparison with CG, in the liver tissue and in brain tissue the content of saturated FAs increased 1.3 times (P <0.05), due to C16: 0 - palmitic, the content of unsaturated FA decreased by 1.3 times (P <0.05), and the proportion of polyunsaturated FA decreased by 1.8 times (P <0.05). Moreover, a change in the liver and brain FA composition the development of T2D was revealed. In the liver of rats with T2D compared with CG revealed an increase of 4 times myristin (P <0,05), 1,4 times of pentadecan (P <0,05) and 2 times (P <0,05) of margarine FA, a reduction of 3.5 times (P <0.05) arachidonic and a 2-fold increase (P <0.05) of linolenic. In the brain of rats with T2D, the content of myristin and pentadecan FA increased by 2-fold (P <0.05), and margarine appeared, which was not detected in the CG rats. Found a 2-fold (P <0.05) decrease in linoleic, a 2-fold increase in arachidone (P <0.05), and determined a linolenic that was not characteristic of CG rats. Modeling T2DM by feeding of HFD with the addition of fructose and the induction of STZ causes not the same redistribution of the fatty acid composition of the organs of experimental animals. This must be taken into account for prescribing a therapeutic scheme (diet) that is targeted correction of the FA, since the treatment results can affect the functioning of organs differently and body systems.